Gonzalo Rojas and Maoist China: essay, poetry and the Dao De Jing (Castilla. Estudios de Literatura, 2026)
Growing connections between Chile and the People’s Republic of China have led to the unveiling of a group of authors whose works were put at the service of these cultural bridges already in the fifties. Among those travelers was the poet Gonzalo Rojas, who expressed his testimony on the developing Maoist society within 1959 and 1972. Hence, the following pages show how this experience was as connected to his Latin American project at the University of Concepción as it was to the imprint of Tao Te King [Dao De Jing] in his poetry.
Keywords: Taoism; Latin American poetry; China; Maoism